2015
DOI: 10.1016/j.psychsport.2014.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Motor ability and self-esteem: The mediating role of physical self-concept and perceived social acceptance

Abstract: Objectives: One important issue in sport and exercise psychology is to determine to what 1 extent sports and exercise can help to increase self-esteem, and what the underlying 2 mechanism might be. Based on the exercise and self-esteem model (EXSEM) and on findings 3 from the sociometer theory, the mediating effect of physical self-concept and perceived social 4 acceptance on the longitudinal relationship between motor ability and self-esteem was 5 investigated. Design: Longitudinal study with three waves of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 58 publications
1
22
1
1
Order By: Relevance
“…This result is (partly) in contrast to other longitudinal studies. Significant associations have been found in both boys and girls, with even stronger associations in boys (e.g., Schmidt, Blum, Valkanover, & Conzelmann, 2015). We have no clear explanation for our results.…”
Section: Differences Between Boys and Girlscontrasting
confidence: 70%
“…This result is (partly) in contrast to other longitudinal studies. Significant associations have been found in both boys and girls, with even stronger associations in boys (e.g., Schmidt, Blum, Valkanover, & Conzelmann, 2015). We have no clear explanation for our results.…”
Section: Differences Between Boys and Girlscontrasting
confidence: 70%
“…It is worth noting that sex has been previously identified to be an important factor influencing physical activity, global self-worth, and internalizing problems in school-aged children. For example, compared to boys, girls have been found to be less physically active ( Cairney et al, 2010 ), have lower levels of self-concept ( Schmidt et al, 2015 ), and report more internalizing problems ( Wade et al, 2002 ). Moreover, a previous study examining the mediating pathways from pDCD to internalizing problems in the ESH found that the underlying mechanisms through physical activity and global self-worth may also be sex specific.…”
Section: Methodsmentioning
confidence: 99%
“…According to Conzelmann and Müller [ 2 ], no convincing proof has yet been provided that sport actually promotes personality development. However, the available data suggests that cognitive personality traits (e.g., self-concept) can be influenced more strongly through sporting activity than by static personality traits (global traits) [ 2 , 3 , 27 ]. Nevertheless, the causal direction here is unclear and cannot be clarified through the methodological approach [ 28 , 29 ].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The relationship between sport participation, personality development, self-concept and self-esteem has repeatedly been discussed within the framework of legitimation discussions in the sector of school sport. The research shows contradictory findings (see [ 1 , 2 , 3 ]). These contradictions concern, inter alia, the direction of causal associations of the investigated features.…”
Section: Introductionmentioning
confidence: 99%